High affinity nanobodies against the Trypanosome brucei VSG are potent trypanolytic agents that block endocytosis. - Benoît Stijlemans (Public Library of Science (PLoS), 2011)
The African trypanosome Trypanosoma brucei, which persists within the bloodstream of the mammalian host, has evolved potent mechanisms for immune evasion. Specifically, antigenic variation of the variant-specific surface glycoprotein (VSG) and a highly active endocytosis and recycling of the surface coat efficiently delay killing mediated by anti-VSG antibodies. Consequently, conventional VSG-specific intact immunoglobulins are non-trypanocidal in the absence of complement. In sharp contrast, monovalent antigen-binding fragments, including 15 kDa nanobodies (Nb) derived from camelid heavy-chain antibodies (HCAbs) recognizing variant-specific VSG epitopes, efficiently lyse trypanosomes both in vitro and in vivo. This Nb-mediated lysis is preceded by very rapid immobilisation of the parasites, massive enlargement of the flagellar pocket and major blockade of endocytosis. This is accompanied by severe metabolic perturbations reflected by reduced intracellular ATP-levels and loss of mitochondrial membrane potential, culminating in cell death. Modification of anti-VSG Nbs through site-directed mutagenesis and by reconstitution into HCAbs, combined with unveiling of trypanolytic activity from intact immunoglobulins by papain proteolysis, demonstrates that the trypanolytic activity of Nbs and Fabs requires low molecular weight, monovalency and high affinity. We propose that the generation of low molecular weight VSG-specific trypanolytic nanobodies that impede endocytosis offers a new opportunity for developing novel trypanosomiasis therapeutics. In addition, these data suggest that the antigen-binding domain of an anti-microbial antibody harbours biological functionality that is latent in the intact immunoglobulin and is revealed only upon release of the antigen-binding fragment.